2015
DOI: 10.1099/vir.0.000086
|View full text |Cite
|
Sign up to set email alerts
|

Tropism of human pegivirus (formerly known as GB virus C/hepatitis G virus) and host immunomodulation: insights into a highly successful viral infection

Abstract: Human pegivirus (HPgV; originally called GB virus C/hepatitis G virus) is an RNA virus within the genus Pegivirus of the family Flaviviridae that commonly causes persistent infection. Worldwide, 750 million people are actively infected (viraemic) and an estimated 0.75-1.5 billion people have evidence of prior HPgV infection. No causal association between HPgV and disease has been identified; however, several studies described a beneficial relationship between persistent HPgV infection and survival in individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 121 publications
(134 reference statements)
2
97
0
2
Order By: Relevance
“…HPgV replicates in peripheral blood mononuclear cells (PBMC) ex vivo, but the primary type of cell(s) that support HPgV replication in vivo are not well characterized (Chivero and Stapleton, 2015). Among chronically infected individuals, HPgV RNA is found in multiple blood cell types including T and B lymphocytes, monocytes and natural killer (NK) cells (Chivero et al, 2014;George et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…HPgV replicates in peripheral blood mononuclear cells (PBMC) ex vivo, but the primary type of cell(s) that support HPgV replication in vivo are not well characterized (Chivero and Stapleton, 2015). Among chronically infected individuals, HPgV RNA is found in multiple blood cell types including T and B lymphocytes, monocytes and natural killer (NK) cells (Chivero et al, 2014;George et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, however, human immunodeficiency (HIV)‐HPgV association studies were extensively explored, due to a possible beneficial effect in HIV infection motivating investigations about HIV‐HPgV interactions at the molecular level . Mechanisms of viral persistence and host‐immune modulation remain also poorly characterized . Previous studies allowed the identification of the viral genome in liver, spleen, bone marrow, and peripheral blood mononuclear cells, including T and B lymphocytes, NK cells, and monocytes; the infection of progenitor hematopoietic stem cells as possible primary targets of the virus had been also suggested …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed frequent detection of pegivirus GBV-C (HPgV, referred herein as HPgV-1) in HCV-infected individuals [3,15]. Since HPgV-2 was discovered in an HCV coinfected individual (UC0125.US), initial screening of 200 plasmapheresis donors positive for HCV by NAT and Ab testing (HCV NAT+/Ab+) was performed for HPgV-2 using a real-time RT-PCR directed against a region spanning the NS2 and NS3 genes (S2A Fig).…”
Section: Hpgv-2 Strain Diversity and Phylogenymentioning
confidence: 99%